Reliability Thermal Design, Simulation and Experimental Verification of Electronic Monitoring Unit for Magnetic Resonance System - Tingwei LIU; Cunli ZHANG; Yahong WANG; Huaiyu Dong; Yuehan JIN (Zhongguo yiliao qixie zazhi)
The monitoring unit used in the nuclear magnetic resonance system, as an important unit of the system, faces a high thermal risk during its entire life cycle. This paper ensures the high efficiency and reliability of the thermal design of the product module from the two dimensions of structural design and device derating design. In order to reduce the risk of thermal design of electronic modules and comprehensively verify the effectiveness of thermal design of electronic modules, the design verification is carried out by combining simulation and experiment. In the simulation process, by establishing a thermal simulation model at the circuit board level, the crustal temperature of the core device is numerically calculated, and the index is compared with the thermal design index value and the test value, on the one hand, to verify the correctness of the simulation model. On the other hand, the validity of thermal design is verified. In the testing process, a thermal test platform for product modules is built, and the thermal characteristics test values of the core components of the module under extreme electrical conditions are obtained, and the corresponding conversion methods are used to predict the thermal performance and thermal design margin of the product at different altitudes. The results show that the electronic module can meet the thermal design requirements in terms of structural design and derating design of core components, and can ensure that the product module can work safely and reliably during the entire life cycle of the NMR system.